Fruit species of Rondónia State center-south, Especies frutíferas do centro-sul do Estado - Rodrigues Rodrigues; Caetano N Diego G. Caetano N G.; Maria Caetano Creucí Maria (Acta Agronómica)
his work constitutes the first survey of fruitful species of Rondónia State, in the Brazilian Amazon. This started in 2005, until now 22 species had been catalogued, distributed in 13 botanical families. Among the families Palmae and Sterculiaceae have been distinguished, each one with five described species. Some species are not part of the popular knowledge, being consumed mainly for the wild fauna, as Diospyros brasiliensis Mart. (caqui-do-mato), Bellucia grossularioides (L.) Triana (jambinho) and Maclura tinctoria (L.) Engl. (amoreira). Beyond the nourishing use, some species present new potentials, case of aÃ§aí Euterpe oleracea Mart., whose seeds are used in the manufacture of â€œbio-jewelsâ€. Este trabalho se constitui no primeiro levantamento de espécies frutíferas do Estado de Rondónia, na Amazónia brasileira. Iniciado em 2005, até o momento foram catalogadas 22 espécies, distribuídas em 13 famílias botÃ¢nicas. Entre as famílias destaca-se Palmae e Sterculiaceae, cada uma com cinco espécies descritas. Algumas espécies nÃ£o fazem parte do conhecimento popular, sendo consumidas principalmente pela fauna silvestre, como Diospyros brasiliensis Mart. (caqui-do-mato), Bellucia grossularioides (L.) Triana (jambinho) e Maclura tinctoria (L.) Engl. (amoreira). Além do uso alimentício, há espécies que apresentam novos potenciais, caso do aÃ§aí Euterpe oleracea Mart., cujas sementes sÃ£o utilizadas na fabricaÃ§Ã£o de biojóias.